Novel cell sources for bone regeneration. Issue 2 (4th May 2021) - Li, Chenshuang; Mills, Zane; Zheng, Zhong
Abstract: A plethora of both acute and chronic conditions, including traumatic, degenerative, malignant, or congenital disorders, commonly induce bone disorders often associated with severe persisting pain and limited mobility. Over 1 million surgical procedures involving bone excision, bone grafting, and fracture repair are performed each year in the U.S. alone, resulting in immense levels of public health challenges and corresponding financial burdens. Unfortunately, the innate self‐healing capacity of bone is often inadequate for larger defects over a critical size. Moreover, as direct transplantation of committed osteoblasts is hindered by deficient cell availability, limited cell spreading, and poor survivability, an urgent need for novel cell sources for bone regeneration is concurrent. Thanks to the development in stem cell biology and cell reprogramming technology, many multipotent and pluripotent cells that manifest promising osteogenic potential are considered the regenerative remedy for bone defects. Considering these cells' investigation is still in its relative infancy, each of them offers their own particular challenges that must be conquered before the large‐scale clinical application. Abstract : A plethora of both acute and chronic conditions, including traumatic, degenerative, malignant, and congenital varieties, often play key roles in reducing the quality of life for many people. This is particularly true in the case of critical‐size defects where the innate self‐healing capacity of bone is inadequate for a reunion. To date, a diversity of novel multipotent/pluripotent cell sources are regarded as regenerative medicine, particularly for bone regeneration, in virtue of continued worldwide collaboration. Although their potential is irrefutable, each of the cell sources mentioned has its own drawbacks, which must be entirely understood and overcome before they are released for human clinical application.